A Eulerian-Lagrangian approach for the CFD analysis of airborne disease transmission in a car cabin. Issue 1 (1st April 2022) - Grossi, G.; Arpino, F.; Buonanno, G.; Cortellessa, G.; Moretti, L.; Nagano, H.; Stabile, L.
Abstract: In indoor environments such as private cars, taxis and public transport, social distance cannot always be applied and virus concentrations can reach high levels. In this paper, a Eulerian-Lagrangian approach is adopted for the transient simulation of aerosol airborne dispersion in a passenger car cabin. The numerical tool, validated by PIV analysis, is applied to study three different scenarios during the respiratory activity. The car ventilation system and the position of the passengers affect the mass of inhaled aerosol and consequently the quality of the passenger compartment air.